Implementation of Pragmatic Stream Principles in Islamic Education Learning: Efforts to Realize Adaptive and Solutive Education - Dhini Maulidatul Isnaini; Abdul Khobir; Nilna Zulfa; Ika Nur Iliza (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2025)
The development of the modern era marked by globalization, digitalization, and the complexity of social problems requires Islamic Education to be adaptive and solution-oriented. However, Islamic Education learning still tends to be normative and insufficiently connected to students’ real-life contexts, thus necessitating a relevant philosophical and pedagogical approach. This study aims to analyze the principles of the pragmatic school of thought and their implementation in Islamic Education learning to realize adaptive and solution-oriented education. This research employs a qualitative approach using a library research method. Data were obtained from books, scholarly journal articles, and relevant academic documents. Data collection was conducted through source selection, critical reading, and systematic note-taking. Data were analyzed using descriptive-analytical content analysis techniques. The findings indicate that pragmatic principles such as experiential learning, problem solving, inquiry-based learning, technological integration, and performance-based assessment are compatible with the values of Islamic Education. The implementation of these principles enhances learning relevance, strengthens character development, and makes Islamic Education more contextual in addressing modern challenges. The implementation of pragmatism in Islamic Education strengthens the integration of knowledge and action, making learning more applicable, adaptive, and responsive to contemporary social dynamics. The novelty of this study lies in the conceptual synthesis of educational pragmatism with Islamic values as a foundation for adaptive and solution-oriented learning.